'Entre el alivio y el palo': a Spanish trans man's narrative of transitioning in middle age. (3rd July 2018) - Gray, John
Abstract : This paper draws on a series of life story interviews with Lukas, a middle-aged Spanish trans man who was previously ascribed the identity of butch lesbian. Specifically it draws on four interviews which date from the months following Lukas's initial self-identification as trans in late 2015. The interviews capture a transitory moment in his gender transitioning. The paper addresses the intersectionalityof gender and sexuality and focuses mainly on the way in which Lukas's claiming of his trans man identity simultaneously articulates with his repudiation of his former lesbian identity. In these interviews Lukas presents himself as caught between what he describes as 'el alivio' ('the relief') of initial self-recognition, and 'el palo' ('the hassle') of deciding what do next. The hassle arises from the fact that he has what he describes as 'una vida hecha ya' (literally 'a life already made' for himself), and because many of the choices before him have financial and professional implications. Most significantly however, the hassle is also shown to be inextricably bound up with the 'neglected intersectionality' of age.